Changing Dynamics of Trade in India - Gill, Ria (Thapar Institute of Engineering & Technology, Patiala, 2019)
Indian economy and foreign trade are on a growth route. Indian exports have come a long way in value terms from the time of gaining independence in 1947. The total value of Indian merchandise exports increased from US $ 1.3 billion in 1950-51 to US $ 63.8 billion in 2003-04 a compound rate of 7.6 per cent. Trade growth has picked up post liberalization of 1991. The present study makes an analysis of various sectors in Indian economy. The paper also makes an analysis of India and other South Asian countries through examining its growth and contributions in the economy. The composition of trade is now dominated by manufactured goods and services. India services exports share in global exports is more than double of that of Indian manufacturing exports. This study also covers the top 15 items of imports and exports.
Keywords: Exports; Imports; Trade; India